The science-practice interface in Ecology and Conservation: a conceptual framework and shared ways of thinking among scientists and decision-makers - Garcia, Diana Bertuol (2017)
Many current debates in Ecology and Conservation Science center on how to navigate the interface between science, policy and practice with the aim of using science to support viable, effective solutions to environmental problems. This dissertation has the general aim of contributing to devise ways to navigate the science-practice interface by taking an interdisciplinary approach to identify (1) how the academic debate on this subject has been framed, and (2) how scientists and decision-makers have been thinking about the relationship between science and practice. In chapter 1, I present a literature review, based on 1563 sentences describing causes of the science-practice gap extracted from 122 articles published in Ecology and Biodiversity Conservation journals. I use text analysis techniques to organize these causes into a process-based conceptual framework that describes three perspectives on the important processes, knowledges and actors in the science-practice interface. I then evaluate the predominance of these perspectives over time and across journals, and assess them in light of disciplines studying the role of science in decision-making, such as Political Science. The unchanged predominance over time of the perspective centered on a linear, unidirectional flow of scientific knowledge from science to practice suggests debates in Ecology and Conservation lag behind trends in other disciplines towards perspectives focusing on a bidirectional, integrative flow of knowledges between science and practice. In Ecology and Conservation, the integrative perspective seems primarily restricted to research traditions historically isolated from mainstream Conservation Biology, which in turn has been dominated by \"evidence-based conservation\" approaches. All identified perspectives represent superficial views of decision-making by not accounting for limits to human rationality, complexity of decision-making contexts, fuzzy science-practice boundaries, ambiguity brought about by science, and different types of knowledge use. Nonetheless, the integrative perspective emphasizing collaborative work between scientists and decision-makers may potentially allow for more democratic decision-making processes and explicit discussions of values. In chapter 2, I focus on scientists and decision-makers from Brazil, a tropical developing nation with a growing science and rich biodiversity, but currently facing several drawbacks in environmental policies. I used the three perspectives of the conceptual framework of chapter 1 to create a list of 48 statements describing how the science-practice interface should ideally be. Using Q-methodology from psychology, I asked 22 ecologists and environmental federal analysts to rank their agreement with these statements. Principal component analysis revealed three groups of participants with similar rankings of statements, thus holding shared ways of thinking about the science-practice interface. All ways of thinking assigned great importance to actors and knowledges from both science and practice, but differed on the roles assigned to science, scientists or decision-makers, indicating the need to openly debate expected roles for each actor in science-practice partnerships. Moreover, such partnerships seem to be hindered by a lack of organizational incentive rather than by cultural differences between scientists and decision-makers. In the final session of the dissertation, I integrate the conclusions from both chapters, highlighting the most important implications for a better understanding of the science-practice interface and for fostering productive science-practice linkages in Ecology and Conservation